Variation of Musa spp. in West Kalimantan, Indonesia, Based on rbcL Chloroplast DNA - Sunandar, Ari; Fajri, Hayatul; Qurbaniah, Mahwar (HAYATI Journal of Biosciences, 2024)
West Kalimantan is home to Musa spp. conservation and genetic assessment of wild banana relatives are important for future breeding purposes. The present study aims to evaluate the genetic relationship of Musa spp. in West Kalimantan by analyzing the rbcL chloroplast DNA using phylogenetic analysis. The methods in this study were sampling, DNA extraction, PCR of rbcL fragment, and data analysis. The specific primer was used to amplify the rbcL chloroplast DNA of ten accessions of Musa spp. in West Kalimantan. The results showed that the area of the rbcL region of Musa spp. in this study was estimated at 587-591 bp. It showed high variability with a conservation level A+T content of 56.95%. The rbcL sequences of Musa spp. have polymorphic sites on 13 numbers of nucleotides. The phylogenetic analysis with an ML algorithm of 35 Musa spp. from West Kalimantan and GenBank data was successfully divided into 4 main clades, and the bootstrap value was 80-81%. This study is expected beneficial for taxonomic, conservation, and banana breeding efforts.